Perceived competition in agricultural lending: Stylized facts and an agenda for future research - Todd H. Kuethe; Chad Fiechter; David Oppedahl (Federal Reserve Bank of Chicago, 2021)
Purpose: This study examines agricultural lending by commercial banks and the competition they face from the Farm Credit System and non-traditional lenders, including merchants, dealers, and other input suppliers. Design/methodology/approach: We construct a measure of commercial banks' perceived competition with FCS or non-traditional lenders using the individual responses to the Federal Reserve Bank of Chicago's Land Values and Credit Conditions Survey between 1999 and 2019. Through regression analysis of an unbalanced panel of survey responses, we present a number of stylized facts on the relationship between perceived competition and farm loan rate spreads, collateral requirements, loan delinquencies, and expected lending volumes. Findings: Our analysis shows that the two sources of competition have very different effects on commercial bank lending terms, loan portfolio riskiness, and expected loan volumes. With these results in mind, we offer a number of suggestions for future research. Originality/value: We leverage the unique characteristics of the Land Values and Credit Conditions Survey to examine the competition with non-traditional lenders that cannot be observed using administrative data.
Keywords: Q14; G21; 330; competition; agricultural lending; non-traditional lenders